The Influence of Home Literacy Environment on Reading Motivation in Middle Childhood - Hasanah, Uswatun; Harahap, Rahimul (Budapest International Research and Critics University, 2023)
Nowadays, children spend more time in front of the screen (television) than reading books and completing reading. The main aim of this research is to determine the influence of the home literacy environment on reading motivation in middle childhood. Respondents in this study totaled 270 people. The sampling method used was purposive sampling. Data were analyzed using simple regression via the SPSS 21 for Windows program. The research results obtained R2 = 0.093 (p = 0.000) for the influence of the home literacy environment on intrinsic reading motivation. Meanwhile, for the influence of the home literacy environment on extrinsic reading motivation, R2 = 0.123 (p = 0.000). This means that the home literacy environment has a significant effect on the dimensions of intrinsic reading motivation and extrinsic reading motivation in middle childhood. The results imply that children who have more opportunities to engage in reading activities at home tend to have more positive views about reading and are more involved in reading activities.